Characterization of chilling-shock responses in four genotypes of Miscanthus reveals the superior tolerance of M. × giganteus compared with M. sinensis and M. sacchariflorus - Purdy, Sarah Jane (Oxford University Press, 2013)
BACKGROUND AND AIMS: The bioenergy grass Miscanthus is native to eastern Asia. As Miscanthus uses C(4) photosynthesis, the cooler temperatures experienced in much of northern Europe are expected to limit productivity. Identification of genetic diversity in chilling tolerance will enable breeders to generate more productive varieties for these cooler regions. Characterizing the temporal relationships between photosynthesis, carbohydrate and molecular expression of relevant genes is key to understanding genotypic differences in tolerance or sensitivity. METHODS: To characterize chilling responses in four Miscanthus genotypes, plants were exposed to a sudden reduction in temperature. The genotypes studied comprised of two M. sinensis, one M. sacchariflorus and one inter-species hybrid, M. × giganteus. Changes in photosynthesis (A(sat)), carbohydrate composition and the expression of target transcripts were observed following chilling-shock. After 4 d the decline in leaf elongation rate (LER) in the different genotypes was measured. RESULTS: Following chilling-shock the greatest decline in A(sat) was observed in M. sacchariflorus and one M. sinensis genotype. Carbohydrate concentrations increased in all genotypes following chilling but to a lesser extent in M. sacchariflorus. Two stress inducible genes were most highly expressed in the genotypes that experienced the greatest declines in A(sat) and LER. Miscanthus × giganteus retained the highest A(sat) and was unique in exhibiting no decline in LER following transfer to 12 °C. CONCLUSIONS: Miscanthus × giganteus exhibits a superior tolerance to chilling shock than other genotypes of Miscanthus. The absence of sucrose accumulation in M. sacchariflorus during chilling-shock suggests an impairment in enzyme function. A candidate transcription factor, MsCBF3, is most highly expressed in the most sensitive genotypes and may be a suitable molecular marker for predicting chilling sensitivity.